Comparison on effects of temperature on different strains of phytase producing bacteria isolated from Malaysia’s hot spring - Nurul Asma Hasliza, Zulkifly; Afnani, Alwi@Ali; Nadiawati, Alias (Penerbit Universiti Sultan Zainal Abidin, 2020)
The main purpose of this research was to find the best growth curve for bacterial growth and the optimum temperature for the production of phytase from different potential phytase producing bacterial strains. A total of four strains used were originally isolated from hot springs in Malaysia, which were in Labis, Johor (L3), Dusun Tua, Selangor (RT), Ulu Legong, Kedah (A) and Ranau, Sabah (B9). Nutrient Agar (NA) and modified Phytase Screening Medium (PSM) liquid media were used for the culture enrichment while optimisation was carried out through batch culture method using a shake-flask scale. Strains growth and enzyme activity were quantitatively measured at different temperatures at (30°C and 37°C) values. Enzyme activity was determined according to the reaction of the phytase with its substrate (sodium phytate) and expressed in units of phytase activity (U/ mL). As for the overall, strain L3 (from Labis, Johor) exhibit promising rate of Pi released in the media at 30°C and 37°C, with optimum phytase activity values of 0.2047 U/mL and 0.2195 U/mL, respectively. The pH of the cultures was also measured, where it shows that strains grown in cultures at 37°C produced a higher phytase activity and resulting a lower reading of pH compared when grown at 30°C. All around, L3 strains has the lowest value of pH when cultured at 30°C and 37°C, with the pH value of 3.62 and 2.37, respectively. From the result obtained, the lower pH indicates the process of phytic acid degradation take place by the phytase in producing inorganic phosphate (Pi) due to the accumulation of organic acid. Since these bacterial strains were originally taken from Hot Springs, further analysis of temperature optimization using 55°C and even 60°C should be carried out. In the future, biochemical research and molecular identification may also be carried out to identify molecular identity in the strains.